HUBUNGAN PENGETAHUAN, JARAK KEHAMILAN DAN FREKUENSI KUNJUNGAN ANC DENGAN KEJADIAN KEKURANGAN ENERGI KRONIK (KEK) PADA IBU HAMIL DI WILAYAH PUSKESMAS 7 ULU KOTA PALEMBANG TAHUN 2024 - Mahpiroh, Dekis; Fika Minata Wathan; Erma Puspita Sari; Minarti (JURNAL KESEHATAN INDRA HUSADA, 2025)
Chronic Energy Deficiency (CED) is the condition where a pregnant woman is deprived of nutrition for a long period of time which is characterized by a LILA size less than 23,5 cm. The aim of this study is to determine the relationship among knowledge, pregnancy spacing, frequency of ANC visits, and the incidence of Chronic Energy Deficiency (CED) among pregnant women. Factors that influence Chronic Energy Deficiency include: age, education, knowledge, economy, pregnancy spacing, ANC frequency, history of illness, parity, husband’s support and the role of health workers. This study used a cross-sectional approach which was conducted at Tujuh Ulu Community Health Centre Palembang on June 25, 2024 – June 29, 2024 by using univariate and bivariate analysis. The results obtained from the 81 respondents studied were 16 (19,8) respondents experienced CED, and 65 (80,2) respondents did not experience CED. Additionally, 21 respondents (25,9%) had less knowledge, 29 respondents (35,8%) had high risk pregnancy spacing, and 10 respondents (12,3%) had less frequency of ANC visits. The chi-square test revealed significant relationships between knowledge and the incidence of CED, with a p-value of 0.000, and between pregnancy spacing and the incidence of CED, with a p-value of 0.028. However, no significant relationship was found between the frequency of ANC visits and the incidence of CED, with a p-value of 0.102. It can be concluded that there is no relationship among knowledge, pregnancy spacing, and frequency of ANC visits simultaneously with the incidence of CED among pregnant women at 7 Ulu Community Health Centre in Palembang City. It is suggested that health workers at 7 Ulu Community Health Centre should increase counselling regarding the danger of CED and how to solve it so that the incidence of CED could be reduced